DIFFERENT APPROACHES IN MANAGING LENS-INDUCED ANGLE CLOSURE GLAUCOMA: A SERIAL CASE: Poster Presentation - Case Series - Resident - Wardani, Sabrina Indri; Rifada, R. Maulana; Prahasta, Andhika; Gustianty, Elsa; Umbara, Sonie (Majalah Oftalmologi Indonesia, 2023)
Introduction : Lens-induced angle-closure glaucoma can be caused by phacomorphic lens and ectopia lentis. Several factors affect the disease progression. Early diagnosis and appropriate management are important. Case Illustration : Case 1. A 67-year-old woman presented with acute redness and blurred vision in her left eye with visual acuity (VA) of 1/300 and intraocular pressure (IOP) of 60 mmHg. Axial length showed 23.66 mm and anterior chamber depth (ACD) was 1.61mm (Figure1). She was diagnosed with phacomorphic glaucoma. Phacoemulsification combined with trabeculectomy was performed (Figure2&3). Her VA was improved to 0.08 and her IOP was reduced to 19mmHg after surgery. Case2. A 67-year-old man came with painful blurred vision in his right eye. His VA was a perception of light with an IOP of 40 mmHg. He had axial length of 22.7 mm and ACD of 2.07 mm (Figure4). The lens was anteriorly subluxated and showed zonular laxity. Intracapsular cataract extraction combined with trabeculectomy was performed (Figure5&6). His VA was unchanged while his IOP was reduced to 18 mmHg after surgery. Discussion : Age older than 60 years old, female gender, short axial length (<23.7 mm), shallow ACD, and zonular laxity are factors for progressivity of lens-induced glaucoma. Cataract removal was a definitive treatment along with IOP-lowering medications. The choice of lens extraction technique varies among individuals. Conclusion : Removal of cataractous lens is a definitive treatment in conjunction with intraocular pressure and inflammatory regulations for managing lens-induced angle-closure glaucoma. Comprehensive clinical assessments in patients are necessary for managing the symptoms and preventing complications.